Effect of lycopene on titanium implant osseointegration in ovariectomized rats - Xiaojie Li; Wenli Xue; Yong Cao; Yanming Long; Mengsheng Xie (Journal of Orthopaedic Surgery and Research, 2018)
Abstract Background Lycopene prevents bone loss in osteopenic models. However, the role of lycopene in the success rate of dental implants under osteopenic conditions remains unknown. The aim of this study was to evaluate whether lycopene prevents delayed implant osseointegration in an ovariectomized (OVX) rat model. Methods Thirty female Sprague-Dawley rats were randomly divided into the following groups: OVX with vehicle (OVX group), OVX with lycopene (OVX + lycopene group) and sham-operated with vehicle (sham group). Twelve weeks after ovariectomy or sham operation, titanium implants were placed into the distal metaphysis of the bilateral femurs of each rat. These rats were subsequently gavaged with lycopene (50 mg/kg/day) or vehicle. After 12 weeks of gavage, all rats were sacrificed, and specimens were harvested. Sample osseointegration was evaluated by biomechanical testing, 3D micro-computed tomography (micro-CT) analysis and histomorphometric analysis. Results Compared with the OVX group, the OVX + lycopene group showed a 69.3% increase in the maximum push-out force (p < 0.01). Micro-CT data for the femurs in the OVX + lycopene group showed significantly higher bone volume, trabecular thickness and less trabecular space than did those in the OVX group. The bone area (BA) around the implant and bone contact (BC) with the implant were increased by 72.3% (p < 0.01) and 51.4% (p < 0.01) in the OVX + lycopene group, respectively, compared with those in the OVX group. There was no significant difference in the mechanical test, micro-CT scanning and histomorphometric data between the OVX + lycopene and sham groups (p > 0.05). Conclusions Lycopene improved implant osseointegration, fixation and bone formation under osteopenic conditions, suggesting that lycopene is a promising therapeutic agent to prevent delayed implant osseointegration and bone loss under osteopenic conditions.